Analisis Strategi Bauran Pemasaran Wisata Alam Gosari (WAGOS) dalam Meningkatkan Jumlah Wisatawan (Studi di Desa Gosari Kecamatan. Ujungpangkah Kabupaten. Gresik) - Asmaul Khuluq; Ahmad Afan Zaini; Fatimatu Zahroh (Al-Muzdahir : Jurnal Ekonomi Syariah, 2021)
The uniqueness of Gosari Gresik Nature Tourism invites local and non-local tourists with various rides offered including Flying Fox, fun outbound, love pool, ATV, mini trail for children, horse riding rides and photo spots with an entrance ticket price of IDR 10,000 for adults and IDR 5000 for children. The management of Gosari Gresik Nature Tourism cannot be separated from the role of youth youth organizations in Gosari village who see the benefits and preservation of the cultural heritage of Majapahit in the remaining area of ​​the pottery industry and inscriptions in Butulan Cave. The marketing mix strategy used is very effective in attracting tourists plus social media which continues to grow, making Gosari tourism increasingly known to foreign countries. But in every management there are obstacles that make tourism managers more qualified